Higher education in southeast Asia - Symaco, Lorraine Pe (Emerald Publishing Limited, 2024)
There is rising interest paid to how higher education is developing across Asia. This timely volume provides readers with a comprehensive account of the higher education systems in one of the most compact regions in the world. The chapters examine ten country case studies grouped in diverse socioeconomic, cultural, and political ecologies. From the and wealthy state of Singapore to mid-economies and multi-ethnic Malaysia, Philippines, and Vietnam, to the most populous Muslim country in the world, Indonesia. Post-conflict states include Cambodia and Timor-Leste; the non-colonial Thailand and recently government-reformed Myanmar; to the socialist state and sole landlocked country in the region, Lao PDR. The authors delve into the role of higher education for broader development and discuss issues relating to the higher education in each country, such as: quality, access, and equity; the roles of globalisation and internationalisation in higher education; governance; sustainable development; social responsibility; aid in education; the role of culture and religion in education; and more. Higher Education in Southeast Asia provides a much-needed new perspective within higher education research, with key findings that have an important impact contextually that are also applicable on an international level.
Includes index.
Keywords: Education, Higher -- Southeast Asia.; Education -- Comparative.; Educational strategies and policy.; Educational systems and structures.; elektronické knihy; electronic books